Advances in sodium-glucose transporter protein 2 inhibitors and tumors - Jiaqi Wang; Wenyong Yang (Frontiers in Oncology)
Tumor is a major challenge to global health and has received extensive attention worldwide due to its high degree of malignancy and poor prognosis. Although the clinical application of targeted therapy and immunotherapy has improved the status quo of tumor treatment, the development of new therapeutic tools for tumors is still necessary. Sodium-glucose transporter protein 2 (SGLT2) inhibitors are a new type of glycemic control drugs, which are widely used in clinical practice because of their effects on weight reduction and protection of cardiac and renal functions. SGLT2 has been found to be overexpressed in many tumors and involved in tumorigenesis, progression and metastasis, suggesting that SGLT2i has a wide range of applications in tumor therapy. The aim of this article is to provide a comprehensive understanding of the research progress of SGLT2i in different tumors by integrating the latest studies and to encourage further exploration of SGLT2i therapies in clinical trials. This could pave the way for more effective management strategies and improved outcomes for tumor patients.